/
/
/
111) f(x, y) = (7x5y3 + 9)2 A) ∂f/∂x = 2(7x5y3
Not my Question
Flag Content

# Question : 111) f(x, y) = (7x5y3 + 9)2 A) ∂f/∂x = 2(7x5y3 : 1757192

111) f(x, y) = (7x5y3 + 9)2

A) f/x = 2(7x5y3 + 9); f/y = 2(7x5y3 + 9)

B) f/x = 42x5y2(7x5y3 + 9); f/y = 70x4y3(7x5y3 + 9)

C) f/x = 70x4y3(7x5y3 + 9); f/y = 42x5y2(7x5y3 + 9)

D) f/x = 35x4y3; f/y = 21x5y2

112) f(x, y) =

113) f(x, y) =

114) f(x, y) = sin2 (-2xy2 - y)

A) f/x = 2sin (-2xy2 - y) cos (-2xy2 - y); f/y = 2sin(-2xy2 - y) cos(-2xy2 - y)

B) f/x = -4y2sin (-2xy2 - y) cos (-2xy2 - y); f/y = 2sin (-2xy2 - y) cos (-2xy2 - y)

C) f/x = 2sin (-2xy2 - y) cos (-2xy2 - y); f/y = (-8x - 2) sin (-2xy2 - y) cos (-2xy2 - y)

D) f/x = -4y2sin (-2xy2 - y) cos (-2xy2 - y); f/y = (-8xy - 2) sin (-2xy2 - y) cos (-2xy2 - y)

115) f(x, y) = ln yx

A) f/x = ln y; f/y = x/y B) f/x = xln y; f/y = - x/y

C) f/x = ln y; f/y = - xln y D) f/x = 0; f/y = - x/y

116) f(x, y) = e-x/x2 + y2

A) f/x = e-x(x2 + y2 + 2x) / (x2 + y2)2 ; f/y = 2ye-x/ (x2 + y2)2

B) f/x = - 2xe-x/ (x2 + y2)2 ; f/y = - 2ye-x/ (x2 + y2)2

C) f/x = - e-x(x2 + y2 + x) / (x2 + y2)2 ; f/y = -ye-x/ (x2 + y2)2

D) f/x = -e-x(x2 + y2 + 2x) / (x2 + y2)2 ; f/y = -2ye-x/ (x2 + y2)2

117) f(x, y) = x/x + y

118) f(x, y) = xye-y

A) f/x = ye-y; f/y = - xye-y B) f/x = ye-y; f/y = xe-y(y - 1)

C) f/x = ye-y; f/y = xe-y(1 - y) D) f/x = ye-y; f/y = xe-y

119) f(x, y) = x3 + 7x2y + 9xy3

A) f/x = 3x2 + 2xy + 9y3; f/y = 7x2 + 3xy2 B) fx = 3x2; f/y = 7x2 + 27xy2

C) f/x = x2 + 7xy + 9y3; f/y = 7x2 + 9xy2 D) f/x = 3x2 + 14xy + 9y3; f/y = 7x2 + 27xy2

120) f(x, y) = x2 + y - ex+y

## Solution 5 (1 Ratings )

Solved
Mathematics 3 Years Ago 64 Views